2023
DOI: 10.3341/kjo.2022.0164
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Lens Applications Focused on Korean Patients with Various Corneal Disorders

Abstract: Purpose: We aimed to report on the clinical outcomes of scleral lens applications in Korean patients with various corneal disorders.Methods: This retrospective review was conducted for 62 eyes of 47 patients who had been fitted with scleral lenses for various corneal disorders. The patients were referred for inadequate spectacle-corrected visual acuity and rigid gas permeable (RGP) or soft contact lens intolerance. Uncorrected visual acuity, habitually corrected visual acuity, best lens-corrected visual acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In the present study, the cases associated with it were a total of 5. Most cases were derived from keratoconus (13,14), which is consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the cases associated with it were a total of 5. Most cases were derived from keratoconus (13,14), which is consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Lee et al evaluated the use of SCL in various corneal disorders, and they also showed statistically significant improvement in BLCVA with contact lenses from UCVA (1.2660.7-0.2160.36 logMAR in corneal scars and 1.3660.85-0.1260.20 logMAR in keratoconus). 3 Along with the improvement in visual acuity, an appreciable improvement in corneal aberrations was also noted in our study. The results were consistent with those shown by Sidi Mohamed Hamida et al 19 and Montalt et al 20 Kumar et al studied the effect of MSL on visual acuity and ocular higher-order aberrations in 15 eyes with keratoconus and concluded that MSL significantly reduced ocular aberrations and improved visual acuity in patients with keratoconus.…”
Section: Discussionsupporting
confidence: 83%
“…Yan et al 9 reported that 91% of patients had comfortable 10-hr daytime lens wear. However, Lee et al 3 in their study found that four eyes of three patients out of 18 eyes of 12 patients using scleral contact lenses for corneal scarring stopped using contact lenses due to insufficient visual quality improvement as they already had good vision with habitual corrected visual acuity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation